2013
DOI: 10.5296/jpag.v3i4.5059
|View full text |Cite
|
Sign up to set email alerts
|

Protection of women rights through legal reforms in Pakistan

Abstract: This paper presents the status of women rights in Pakistan and protection of these rights under the umbrella of legal reforms. After independence the women of Pakistan played an active role in nation building activities as well for their own social uplift. International organizations played special attention towards the issue of women empowerment During Ayub Era Muslim Family Law Ordinance 1961 was promulgated which is regarded as a first step forward for the protection of women rights. During Zia regime discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Literature Review Saeed and Hussain (2010) (Noreen & Mussarat, 2013). The 12th National Assembly, during its tenure from 2002 to 2007, had paved the way for pro-women law.…”
Section: Women Harrasment At Work Place In Pakistanmentioning
confidence: 99%
“…Literature Review Saeed and Hussain (2010) (Noreen & Mussarat, 2013). The 12th National Assembly, during its tenure from 2002 to 2007, had paved the way for pro-women law.…”
Section: Women Harrasment At Work Place In Pakistanmentioning
confidence: 99%
“…[39] Many Pakistanis believe that women deserve to be harassed if they break the stereotype of staying within the premises of their homes and join the male dominated public domain. [40] Pakistani women face a variety of different forms of sexual harassment while moving about in public places, especially when not accompanied by a man. [16,41] The perception of not being safe in public places has been shown to be based on fear of being sexually victimised or raped.…”
Section: Cultural Aspects Of Sexual Harassmentmentioning
confidence: 99%
“…[46] In 2010, an amendment was made in section 509 of the Pakistan Penal Code of 1860, to declare sexual harassment a crime. [40] Still women in Pakistan are unacquainted with the procedure of workplace sexual harassment redress. [20] This is also reflected by the fact that sexual harassment has been the least reported crime in the province of Punjab.…”
Section: Cultural Aspects Of Sexual Harassmentmentioning
confidence: 99%
“…The Table showed that majority of the respondents were in the age group 36-45 years which is a group of mature and well experienced people. The second major age group [25][26][27][28][29][30][31][32][33][34][35] indicates that a majority of the respondents are educated youth serving as representative in the local government. Similarly, among the total 320 (100%); 234 (73.1%) a significant majority is married.…”
Section: Section I: Demographic Profilementioning
confidence: 99%